2019
DOI: 10.3390/cli7040060
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Meteorological Droughts Occurrences in Côte d’Ivoire: Case of the Sassandra Watershed

Abstract: The Sassandra Basin, like most regions of Côte d'Ivoire, is increasingly affected by droughts that involve many environmental, social and economic impacts. This basin is full of several amenities such as hydroelectric dams, hydraulic and agricultural dams. There is also a strong agricultural activity. In the context of climate change, it is essential to analyze the occurrence of droughts in order to propose mitigation or adaptation measures for water management. The methodological approach consisted initially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Artificial dams and small reservoirs were observed at the fringes of some of the areas where we detected natural vegetation losses. The transition of natural vegetation to water bodies may indicate natural flooding or anthropogenic development of pounds and small reservoirs for cropland irrigation, dams for hydro-power generation, urban supply and consumption, as well as other economic purposes [23,24,27,56,86,95,107,[112][113][114][115][116][117][118]. These developments could possibly be explained as adaptation measures adopted in some parts of West Africa to mitigate the impact of the severe drought of the 1970s and the 1980s.…”
Section: Lulc Transitions and Underlying Driving Factorsmentioning
confidence: 99%
“…Artificial dams and small reservoirs were observed at the fringes of some of the areas where we detected natural vegetation losses. The transition of natural vegetation to water bodies may indicate natural flooding or anthropogenic development of pounds and small reservoirs for cropland irrigation, dams for hydro-power generation, urban supply and consumption, as well as other economic purposes [23,24,27,56,86,95,107,[112][113][114][115][116][117][118]. These developments could possibly be explained as adaptation measures adopted in some parts of West Africa to mitigate the impact of the severe drought of the 1970s and the 1980s.…”
Section: Lulc Transitions and Underlying Driving Factorsmentioning
confidence: 99%
“…However, climate change has had an impact on these resources and is expected to increase in the coming days. Climate change, coupled with an ever-increasing population and limited availability of fresh Numerous studies have highlighted the fact that West African watersheds would experience more severe and more frequent droughts (Faye, Sow, & Ndong, 2015;Santé, N'Go, Soro, Meledje, & Goula, 2019). The increase in air…”
Section: Discussionmentioning
confidence: 99%
“…This situation is exacerbated by reduced rainfall observed in West Africa and Côte d'Ivoire. Current studies have shown that the decline in rainfall that began in the early 1970s is continuing [7] [15] [33] [34] [35]. Its effects led not only to a reduction in the operating flow rates of the hydraulic structures but also to a drying up of certain boreholes [36].…”
Section: Discussionmentioning
confidence: 99%